Analytical Solution for the Deformation and Support Parameters of Coal Roadway in Layered Roof Strata. (25th October 2021) - Wang, Kai; Yang, Bao-gui; Wang, Zhong-kui; Wang, Xiao-long
Abstract : In order to meet the security and high-efficiency production needs, high-strength bolt (cable) reinforcement technology is usually used to maintain the stability of roadways. However, due to the great variability of lithology and mechanical properties, the failure form and stability of the layered roof in coal roadways are significant differences. The traditional supporting design method of the layered roof support in coal roadways is the engineering analogy method, which depends on experiences rather than theoretical analysis. Based on the theory of the elastic foundation beam and key stratum, this paper establishes a simplified analytical model of layered roof strata in coal roadways. Based on the Mohr-Coulomb theory, this paper gives the failure criteria of the layered roof strata, and the failure range of the layered roof strata is obtained. The length and pretightening force of bolt (cables) of the layered roof strata can be calculated based on the suspension theory and composite beam theory, which providing a quantitative theoretical basis for the determination of supporting parameters. Finally, as a case, the layered roof strata failure range and supporting parameters of the S1301 auxiliary transportation roadway in Gucheng coal mine are calculated.